The Lignicolous Fungus Hericium erinaceus (Lion’s Mane Mushroom): A Promising Natural Source of Antiradical and DPPH Inhibitory Agents - Akbar Jahedi; Saeideh Ahmadifar; Rahman Mohammadi; Ebrahim Mohammadi Goltapeh (The Scientific World Journal)
Nowadays, the importance of the genus Hericium is increasing due to its nutraceutical and pharmaceutical properties. The main idea of this study is to ingenious management of these wastes to achieve the highest performance of nutrients, minerals, and antioxidant properties using enriched agricultural waste. After preparing mushroom samples, the amount of mineral and mycochemical substances have been respectively evaluated by the Association of Official Analytical Chemists and Folin–Ciocalteu assay. In conclusion, among the fruiting bodies’ samples harvested from 19 substrates, the substrates sawdust 30% + wheat straw 30% + bagasse 15% + rice bran 15% + corn flour 10% recorded the highest phenol and flavonoid contents, with values of 27 mg GAE/g DW ext. and 8 mg QE/g DW ext. as well as the IC50 (88.7 μg/mL). P and K’s highest amounts were recorded with the values of 1833 and 1600 mg/100 g DW, and Fe was recorded with values of 77.7 mg/100 g DW. This study, therefore, provides understandings on the biological technologies for the valorization of organic solid waste into valuable and useful bio-based products.